Precision Molecular Pathology of Neoplastic Pediatric Diseases (Molecular Pathology Library, 2018)
This book provides a comprehensive, state-of-the art review of pediatric oncology. The text covers relevant concepts in molecular biology and addresses technical principles, applications, challenges, and integration of current and emerging genomic and molecular methods in the diagnosis and personalized management of childhood cancers. The text also discusses a wide array of pediatric neoplasms in the context of molecular pathology in a concise and understandable manner, with focus on their molecular pathogenesis, clinicopathological features, classification, molecular diagnosis, and approaches to personalized care. Written by experts in the field, Precision Molecular Pathology of Neoplastic Pediatric Diseases serves as a valuable resource for pathologists, pediatric oncologists, trainees and researchers with an interest in pediatric and molecular pathology. .